Management of the Adult with Congenital Adrenal Hyperplasia. (26th April 2010) - Auchus, Richard J.
Abstract : Congenital adrenal hyperplasia (CAH), most commonly due to 21-hydroxylase deficiency (21OHD), has been studied by pediatric endocrinologists for decades. Advances in the care of these patients have enabled many of these children to reach adulthood. In contrast to the course and management of the disease in childhood, little is known about CAH in adults. In many patients, the proclivity to salt-wasting crises decreases. Linear growth ceases, and reproductive function becomes an issue. Most importantly, management must minimize the potential for long-term consequences of conventional therapies. Here we review the existing literature regarding comorbidities of adults with 21OHD, goals of treatment, and approaches to therapy, with an emphasis on need for improved management strategies.